Pentingnya Pemahaman Teologi Sistematika bagi Misionaris - Obehetan, Yeheskiel (Vieka Wahana Semesta, 2024)
Systematic theology is often perceived as a field of theology that specialises in Christian dogmatics where the scope of study is only related to doctrines based on the Bible. This article aims to examine the importance of understanding systematic theology for missionaries. The method used in this research is a qualitative method with a library research approach. The results of this study show that 1) Systematic theology as the principle of missionary life; 2) Systematic theology as the basis of missionary preaching; and 3) Systematic theology as a material for missionary discipleship. This research is expected to contribute to missionary candidates, missionaries who are preparing to enter the mission field and missionaries who are currently on the mission field.